SH-1028, An Irreversible Third-Generation EGFR TKI, Overcomes T790M-Mediated Resistance in Non-Small Cell Lung Cancer - Han, Luwei; Zhang, Xiaomeng; Wang, Zhiqiang; Zhang, Xian; Zhao, Liwen; Fu, Wei; Liang, Xiaobo; Zhang, Zhibo; Wang, Yong (Frontiers in Pharmacology, 2021)
SH-1028 is an irreversible third-generation EGFR TKI. Both SH-1028 and osimertinib have a pyrimidine structure (a typical mutant-selective EGFR TKI structure). Compared with osimertinib, SH-1028 is modified on the indole ring, thus resulting in a more stable 6,7,8,9-tetrahydro-pyrrolo [1, 2-a] indol structure. In this study, we explored the anti-tumor effect of SH-1028 in vitro and in vivo, the inhibition of cell signal, such as EGFR and ERK phosphorylation, and verified the relationship between the pharmacokinetics and pharmacodynamic responses. Firstly, SH-1028 selectively inhibited EGFR sensitive and resistant mutations, with up to 198-fold more effective compared with wild-type EGFR cells. Then, in mouse xenograft models, oral administration of SH-1028 at a daily dose of 5 mg/kg significantly inhibited proliferation of tumor cells with EGFR sensitive mutation (exon 19 del) and resistant mutation (T790 M) for consecutive 14 days, with no TKI-induced weight loss. Moreover, SH-1028 exhibited good bioavailability, and was distributed extensively from the plasma to the tissues. The main metabolite of SH-1028, Imp3, was tested and showed no wild-type EGFR inhibition or off-target effects. In conclusion, SH-1028 is a new third-generation EGFR inhibitor that exhibits potent activity against EGFR sensitive and resistant (T790 M) mutations.